Faktor Yang Mempengaruhi Keputusan Mahasiswa S1 Ekonomi Islam Fakultas Ekonomi dan Bisnis Universitas Airlangga Belum Menjadi Nasabah Bank Syariah - Mega Nilasari Johan; Ririn Tri Ratnasari (Universitas Airlangga, 2014)
This research aims to determine the factors that influence the decision of Students of Islamic Economics FEB UNAIR not selected as Syariah Bank’s Customer.This research used quantitative methods through exploratory factor analysis. Characteristic of the research population are students of Islamic Economics UNAIR who following the active class. The number of samples in pre eliminary test by conducting a written interview by 25 respondents, and main test required 100 respondents. The sampling technique used is probability sampling. Sampling was done using simple random sampling.Based on the results of the study indicate that there are four factors that affect the decision of Students of Islamic Economics FEB UNAIR. The four factors as a result of reduction of processing factor analysis. These four factors named by factor of the brand image, product knowledge, spurious loyalty, service experience.Advice for the Syariah Bank are improves service experience for every remittance transactions by ontime, Syariah Bank offers interesting sales promotion to get customers, more socialization about negative impact of riba, not burden charge for every transactions in ATM or online banking. Advice for the next researcher, can analys factors made from this research influencing other variabel that decision muslim students S1 FEB UNAIR have not been Syariah Bank’s customer yet, for the second next research, make the factors in this research being exogen variables that influenced muslim consumen behavior to Syariah Bank. REFERENCESAlamsyah, Halim. 2012, Perkembangan dan Prospek Perbankan Syariah Indonesia. IAEI.Anshori Muslich dan Sri Iswati. 2009. Buku Ajar Metodologi Penelitian Kuantitatif. Surabaya: Pusat Penerbitan dan Percetakan UNAIR (AUP).Antonio, Muhammad Syafii. 2001, Bank Syariah Dari Teori ke Praktek. Gema Insani Press bekerja sama dengan Yayasan Tazkia Cendekia.Departemen Agama RI. 2011. Al-Qur'an .Gitosudarmo, Indriyo. 2004. Manajemen Pemasaran. Edisi Pertama Cetakan Keenam.BPFE-Yogyakarta.Kotler, Philip dan AB. Susanto.2001. Manajemen Pemasaran Indonesia. Buku 2.Salemba empat. Jakarta.——–, John Bowen and James Makens. 2002. Pemasaran Perhotelan dan Kepariwisataan.Edisi 2. Jakarta: PT Prenhallindo.——–. 2004. Prinsip-prinsip Pemasaran Jilid II. Jakarta: Erlangga.——–, dan Kevin Lane Keller. 2009. Manajemen Pemasaran. Edisi 14. Jakarta: Erlangga.Malhotra, Naresh K. 2010. Riset pemasaran: Pendekatan Terapan. Jilid 1. Jakarta: PT. Indeks.Ratnasari, Ririn Tri. 2012. Konsep Dasar Syariah Marketing.Slide kuliah Manajemen Pemasaran Syariah. Pertemuan 1.Departemen Ekonomi Islam Fakultas Ekonomi dan Bisnis Universitas Airlangga.——–. 2012. Manajemen Pemasaran Islam. Modul 1. Surabaya: Departemen Ekonomi Syariah Fakultas Ekonomi dan Bisnis Universitas Airlangga.——– dan Nisful Laila. 2012. Measuring Customer Service Quality Based on Fatanah Implementation. Proceedings of 2nd Global Islamic Marketing Conference (GIMC).Abu Dhabi. Solomon, M.R. 1999. Consumer Behaviour : Buying, Having, and Being, 4th Edition. New Jersey 07548; Prentice Hall.Sugiyono.2010. Metode Penelitian Kuantitatif Kualitatif. Bandung: Alfabeta. Sutisna.2001. Perilaku Konsumen dan Komunikasi Pemasaran. Bandung: PT. Remaja Rosdakarya.Wibowo, Edy dan Untung Hendy Widodo. 2005. Mengapa Memilih Bank Syariah?. Bogor: Galia Indonesia.